The diarists of 1940 : an annus mirabilis - Sangster, Andrew, 1945- (Cambridge Scholars Publishing, 2020)
This book examines the integrity of diary keeping and selects seven major diarists from Germany, Italy and Britain who wrote their diaries as the events of 1940 unfolded. They wrote without the benefit of hindsight, and any additional notes a few of them added later are ignored here unless critical. The volume explores how these people understood what was happening in this critical year as it occurred. A few other diarists are quoted, but the seven chosen have been selected for their importance, namely Ulrich von Hassell (a German diplomat and anti-Nazi); Galeazzo Ciano, the Italian Foreign Minister (and Mussolini's son-in-law); Sir John Colville, Lord Alanbrooke, Victor Klemperer, Paul Joseph Göbbels, and George Orwell